Varicella pneumonia associated with spontaneous popliteal arterial thrombosis in an adult: a case study and review of the literature. Issue 3 (September 2014) - Smithson, Alex; Ruiz, Jessica; Ramos, Xavi; Niño, Esther; Armestar, Fernando
Abstract : Introduction: Chickenpox is generally a childhood exanthematic benign self‐limited disease. In contrast, most complications and fatal cases occur among adults, which is the group that suffers less commonly from this disease. The frequency of chickenpox in adults is increasing worldwide, together with the associated complications, mainly varicella pneumonia, which can lead to death. The incidence of other complications such as peripheral artery thrombosis is much lower but can cause important morbidity. Case presentation: We report the case of a 63‐year‐old male smoker, who was otherwise previously healthy, who was admitted to the Emergency Department with chickenpox and varicella pneumonia with respiratory insufficiency requiring mechanical ventilation and intensive care unit admission. During hospitalization, the patient developed spontaneous popliteal artery thrombosis that finally led to transfemoral amputation. Conclusions: Varicella pneumonia and peripheral artery thrombosis are two of the known complications of chickenpox. Both complications seem to be much more frequent in men with an active smoking habit. Clinicians should be aware of these complications in order to recognize them promptly and provide adequate treatment.